Assessment of Antimicrobial and Antioxidant Activities of Four Ethnomedicinal Plants Used by Magars in Nawalpur District, Nepal - Nemkul, Chandra Mohini; Bajracharya, Gan Bahadur; Shrestha, Ila (Journal of Plant Resources, 2022)
Ethnobotanical survey in the Magar villages in Nawalpur district, Gandaki province, Nepal revealed that root of Phanera vahlii (Wight & Arn.) Benth, bark of Rhododendron arboreum Sm. and flower of Woodfordia fruticosa (L.) Kurz, have been in use for diarrhea and dysentery. Root of Thalictrum foliolosum DC. has been used for the treatment of rheumatic pain. The study aimed to evaluate antimicrobial and antioxidant effects as well as total phenol content in Phanera vahlii, Rhododendron arboreum, Woodfordia fruticosa and Thalictrum foliolosum. Total phenol content (TPC) was estimated using Folin-Ciocalteu method. 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) free radical and hydrogen peroxide scavenging assays were used to evaluate the antioxidant capacity. Antibacterial effect was established by the Agar well diffusion assay. The minimum TPC value of 65.78±3.44 mg GAE/g dry extract was estimated in 70% methanolic extract of Thalictrum foliolosum and maximum TPC value of 258.40±6.26 mg GAE/g dry extract was estimated in 70% methanolic extract of Woodfordia fruticosa. IC50 value range 21.59±0.26 µg/ml in Rhododendron arboreum to 1124.79±3.69 µg/ml in Thalictrum foliolosum was calculated in DPPH free radical scavenging assay. Scavenging of DPPH free radical range from 12.40% to 94% at 100 µg/mL concentration of 70% methanolic extracts were estimated and scavenging of hydrogen peroxide range from 36% to 73%. The maximum zone of inhibition (ZOI) against Escherichia coli at loading dose of 5 mg of the extract observed was 18±0.73 mm by 70% methanolic extract of Woodfordia fruticosa and its minimum inhibition concentration (MIC) was <1.56 µg /ml.The extracts efficiently inhibited the growth of Escherichia coli verifying the rural knowledge. At the same time, the extracts displayed efficient antioxidant activity.